Acetabular fractures: Is it possible to regain the same patient's related quality of life before trauma?. (November 2018) - Piazzolla, A.; Baglioni, M.; Solarino, G.; Vicenti, G.; Panella, A.; Moretti, B.
Abstract: Introduction: acetabular fractures are difficult to treat with often an unsatisfactory results for patients. The aim of this study is to investigate about the health-related quality-of-life outcome of patients with a traumatic acetabular fracture, as recorded at least 24 months after their surgery. Methods: a cohort of patients underwent a dedicated acetabular surgical reconstruction for a pelvic trauma between November 2011 and May 2016, were enrolled to investigate, at least two years after injury, their midterm quality of life; SF-36 and LiSat-11 were used. Results: 35 patients were enrolled but only 28 patients were revisited, 20 males (714%) and 8 females (286%) with a mean age of 43 years (19–73). The most common cause was motor vehicle accident (655%). Lower score after trauma are reported in both tests, SF-36 and LiSat 11, for all items. Discussion: comparing the SF-36 score in the Italian normative sample with our SF-36 score before the trauma there is no statistically significant difference (p = 0.1661) underlining how the patients before the trauma were healthy and in good health. Both scores, SF-36 and LiSat-11, before and after trauma are statistically different with respectively p = 0, 0002 and p = 0, 049 which proves the lower quality of life after trauma in comparison to their life before trauma. Conclusions: Although the treatment protocols of acetabular fractures have greatly improved over the years, these continue to have disabling consequences that hardly allow to recover a good quality of life two years after the trauma.